(untitled) (Asian Education Studies, 2018)
This study aims to investigate EFL pre-service teachers’ perceptions of CLIL concerning what CLIL is, what CLIL provides, what CLIL requires, who should implement CLIL, and where CLIL teachers should be trained. The participants were EFL pre-service teachers studying in the faculty of education, Mahasarakham University, Thailand. Questionnaires were used to collect the data after the introduction of CLIL. The findings revealed that most of the participants knew the notion of CLIL as they had taken the teacher training course. The majority of the participants viewed that CLIL provided the opportunities to integrate language into the content subjects. They believed that CLIL helps students develop both language skills and subject knowledge. However, it was revealed that the difficulties in CLIL implementation concerned content, a combination of culture to the lesson, and language (communication). The factors causing the difficulties were mainly related to teachers’ lack of content knowledge, students’ low English proficiency, and the difficult content interrelated to the technical vocabulary. Another factor directly related to CLIL was 4Cs integration into the lessons. It can be seen that although the EFL pre-service teachers have taken the CLIL training course, they still find CLIL difficult to apply and cannot make CLIL classes effective. The factors can be a guide to develop the CLIL training in order to produce qualified CLIL teachers. Content subject and language training, principles of 4Cs and of CLIL, as well as how to apply to the lessons should be highly emphasized in the training course.